Drug Addication in Anantnag : Issues and Challenges - Arshad Majid Rather; Dr. Nazma Khatun (International journal of economic perspectives, 2025)
The use of illicit drugs has become a major public health issue in the Anantnag district of India’s Jammu and Kashmir state. This study aims to identify the causes of this issue and the various factors that contribute to its rise. Among the other factors that have contributed to the rise of addiction cases are the availability of drugs and the unemployment rate in the region. This article explores the socioeconomic impacts of illicit drugs on different groups, such as families, communities, and the public health system. It also looks into the various challenges that confront the fight against addiction, such as the lack of resources and awareness, as well as social stigma and the establishment of inadequate treatment facilities. The rising number of drug abuse cases in Anantnag has highlighted the need for a comprehensive approach to address the issue. This study aims to identify the various factors that contribute to the development of this problem and the implementation of effective rehabilitation programs. The study seeks to provide a sociological analysis of the problem of drug addiction in Anantnag, and it offers recommendations on ways to address its impacts.